Genetic programs of neuronal degeneration in dendrite arborization neurons. - Yap, Kar Wei. (2011)
Pruning is an important neuronal remodeling process that fine-tunes the neuronal circuit and it was found to share similarities with neurodegenerative diseases. However, the underlying mechanisms of pruning remained unknown. Here, we used the Drosophila dorsal dendritic arborization (ddaC) neurons as a model system to study dendrite pruning. In order to identify genes involved in dendrite pruning, we carried out a genome-wide RNA-mediated gene interference (RNAi) screen using the Gal4-upstream activating sequence (UAS) system. We identified four genes, Female sterile (2) Ketel (Fs(2)Ket), Suppressor of variegation 3-9 (Su(var)3-9), Rpt4 and short wing to be involved in dendrite pruning. Knocking down of these genes resulted in the dendrite pruning defect at 16 hour after puparium formation (APF). Immunostaining results showed that the ecdysone receptor isoform B1 (EcR-B1) level was reduced in the Fs(2)Ket knockdown mutants, suggesting that Fs(2)Ket may work upstream of EcR-B1 signaling. In addition, the downregulated Sox14 and Mical level observed in Fs(2)Ket and Su(var)3-9 knockdown mutants indicated that these two novel genes mediate dendrite pruning by regulating Sox14 and Mical expression. The identification of novel genes helps in elucidating the mechanisms underlying dendrite pruning, possibly aid in the understanding of the molecular pathway of neurodegenerative diseases.